1998
DOI: 10.1097/00007632-199803010-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Manual Versus Computer-Assisted Radiographic Measurement

Abstract: The results of this study demonstrate that intraobserver variability for manual and computer Cobb angle measurements yield a 95% confidence interval of approximately 3 degrees, with the computer having a slightly lower variability. The computer technique removes sources of intrinsic error, e.g., the variability introduced by using different manual protractors, the inaccuracy of standard protractors, and the use of wide-diameter radiographic markers. Identical digital images can be shared electronically between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
109
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 8 publications
5
109
2
5
Order By: Relevance
“…These data suggest that the use of digital measurements does not improve measurement accuracy of the Cobb angle. These findings are in contrast to those reported by Shea et al [11], who found a statistically better correlation in digital, compared to manual measurement of curves. However the intra-and interobserver reliability results of this study are comparable with those from previous studies [2,6,8] (Table 4).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These data suggest that the use of digital measurements does not improve measurement accuracy of the Cobb angle. These findings are in contrast to those reported by Shea et al [11], who found a statistically better correlation in digital, compared to manual measurement of curves. However the intra-and interobserver reliability results of this study are comparable with those from previous studies [2,6,8] (Table 4).…”
Section: Discussioncontrasting
confidence: 99%
“…Important parts of the spine can be enlarged and seen more clearly by changing the contrast, and the borders of the vertebrae can be enhanced by computerized options. After drawing lines through the endplates of end vertebrae the software measures the angle automatically, which may reduce sources of error [11].…”
Section: Discussionmentioning
confidence: 99%
“…First, the mean angular difference was 2.81°±2.61°. The reproducibility of the Cobb angle measures obtained here appears equal to or better than previously reported for intra-observer or inter-observer studies using manual or computer-assisted techniques [4,5,15,17,18,20]. However, direct comparisons cannot be made with the previously mentioned studies because different radiographs were evaluated and differing statistical methods used in those studies.…”
Section: Discussionsupporting
confidence: 52%
“…Studies of inter-observer and intra-observer variability in measurement of this angle [3,7,9,15,16,20] have revealed that errors in radiographic measurements are typically ±5°and are comparable with thresholds of change that can influence treatment decisions [19]. Recent studies [4,5,8,14,18] demonstrate computer-assisted methods to reduce technical errors and the need for memorization of measurement and classification procedures. However, the manual technique is routinely used in many surgical teams because of its simplicity and cost [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation